Global Development Governance 2.0: Fractured accountabilities in a divided governance complex - Sebastian Haug; Jack Taggart (Global Policy, 2023)
The proliferation of state and non-state actors, along with increasing institutional complexity, has led to a qualitative shift in Global Development Governance (GDG) towards what we term `GDG 2.0'. Realising accountability in this context presents challenges due to growing actor diversity, institutional plurality and a lack of formalised accountability structures. Building on the introduction to this special section, we explore the potential of `forward-looking' approaches to accountability, notably collective deliberation, learning and competition. Despite the importance of these mechanisms for GDG processes, conceptualising them as accountability tools may have limited gains and indeed reinforce the preferences of established actors, dilute useful monitoring approaches and divert attention from longstanding agendas. We argue that prioritising enabling environments for more circumscribed `backward-looking' accountability - with a focus on standard-setting and monitoring - may be more feasible and effective towards holding decision-makers to account within the GDG 2.0 context.
Keywords: 320